Maturational Changes in Rabbit Renal Brush Border Membrane Vesicle Osmotic Water Permeability - Quigley, R. (1998)
We have recently shown that the osmotic water permeability (P(f)) of proximal tubules from neonatal rabbits is higher than that of adults (AJP 271:F871-F876, 1996). The developmental change in P(f) could be due to differences in one or more of the components in the path for transepithelial water transport. The present study examined developmental changes in water transport characteristics of the proximal tubule apical membrane by determining P(f) and aquaporin 1 (AQP1) expression in neonatal (10–14 days old) and adult rabbit renal brush border membrane vesicles (BBMV). AQP1 abundance in the adult BBMV was higher than the neonatal BBMV. At 25°C the P(f) of neonatal BBMV was found to be significantly lower than the adult BBMV at osmotic gradients from 50 to 250 mOsm/kg water. The activation energy for osmotic water movement was higher in the neonatal BBMV than the adult BBMV (9.19 ± 0.37 vs. 5.09 ± 0.57 kcal • deg(−1) • mol(−1), P < 0.005). Osmotic water movement in neonatal BBMV was inhibited 17.9 ± 1.3% by 1 mm HgCl(2) compared to 34.3 ± 3.8% in the adult BBMV (P < 0.005). These data are consistent with a significantly greater fraction of water traversing the apical membrane lipid bilayer in proximal tubules of neonates than adults. The lower P(f) of the neonatal BBMV indicates that the apical membrane is not responsible for the higher transepithelial P(f) in the neonatal proximal tubule.